Associated Factor Related to Anxiety on Primigravida Pregnant Women in The Third Trimester on Facing Labor in The Covid-19 Pandemic - Iis Tri Utami; Nopi Anggista Putri; Beniqna Maharani Besmaya; Yuni Sulistiawati; Maulia Isnaini (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
The COVID-19 epidemic has made primigravida mothers even more anxious, and the psychological effects of worry will have a detrimental effect on labor and delivery. The goal of the study was to identify the characteristics that are correlated with anxiety in primigravida pregnant women who are confronting the COVID-19 pandemic in the third trimester of labor. The study was quantitative with a cross-sectional analytical research design, a 63-person sample size, and total sampling as the sampling method. Bivariate data analysis employed the chi-square test, whereas univariate data analysis used percentage frequency distribution. The results showed that results of the chi-square test showed that there was a correlation between age (p-value = 0.000 less than 0.05), education (p-value = 0.019 less than 0.05) and socioeconomic (p-value = 0.001 less than 0.05) with anxiety on pregnant women in the third trimester of a primigravida in dealing with labor during the COVID-19 pandemic. It is expected that healthcare workers will conduct REBT counseling for pregnant women aged less than 20 years and more than 40 years who experience anxiety, and disseminate information about COVID-19. Abstrak: Kondisi pandemi COVID-19 semakin menambah kecemasan pada ibu primigravida, dampak psikologis berupa kecemasan akan memberikan dampak buruk pada proses persalinan. Tujuan penelitian mengetahui faktor – faktor yang berhubungan dengan kecemasan pada ibu hamil primigravida trimester III dalam menghadapi persalinan di masa pandemi COVID-19. Jenis penelitian adalah kuantitatif, desain penelitian analitik dengan pendekatan cross sectional, besar sampel 63 orang, teknik pengambilan sampel menggunakan total sampling. Analisa data univariat menggunakan distribusi frekuensi prosentase dan bivariat dengan menggunakan uji chi square. Hasil penelitian uji chi square terdapat ada hubungan usia (p value =  0,000 kurang dari 0,05), dan pendidikan (p value =  0,019 kurang dari 0,05) dengan kecemasan pada ibu hamil primigravida trimester III dalam menghadapi persalinan di masa pandemi COVID-19. Diharapkan petugas kesehatan melakukan konseling REBT bagi ibu hamil usia kurang dari 20 tahun dan lebih dari 40 tahun yang mengalami kecemasan, melakukan sosialisasi informasi tentang pencegahan COVID – 19.